Dielectric, ferroelectric and piezoelectric properties of the lead free 0.9BaTiO3-(0.1- x)Bi0.5Na0.5TiO3- x Bi(Mg0.5Ti0.5)O3 solid solution - Mayamae, Jitkasem; Sukkha, Usa; Niemchareon, Surasak; Muanghlua, Rangson; Vittayakorn, Naratip (My University, 2016)
Solid solution of 0.9BaTiO3-(0.1-x)Bi0.5Na0.5TiO3-xBi(Mg0.5Ti0.5)O3 (BT-BNT-xBMT) system, where x = 0.00, 0.02, 0.04, 0.06, 0.08, 0.10, was synthesized by the solid state reaction. Dense BT-BNT-xBMT ceramics were obtained by sintering at 1,150-1,250C for 4 h. The effect of BMT on crystal structure and electrical property of BT-BNT ceramics was investigated as a function of composition, x, using X-ray diffraction, dielectric spectroscopy, hysteresis and strain measurements. The crystal structure of solid solution BT-BNT-xBMT, where x = 0.00-0.10, successively transforms from tetragonal to pseudocubic symmetry, with increased BMT concentration. Temperature dependence of dielectric constant (εr) and dielectric loss (tanδ) for BT-BNT-xBMT at various frequencies showed that phase transition of ceramics changed from ferroelectric to relaxor-like behavior as BMT content increased. Furthermore, remanent polarization (Pr), coercive field (Ec) and the normalized strain (d33∗) of BT-BNT-xBMT ceramics tend to decrease with increasing BMT concentration.
Keywords: BT-BNT-xBMT; electrical properties; lead free piezoelectric; phase transition